Novel RUNX2/CBFA1 mutation in the runt domain in a Japanese patient with cleidocranial dysplasia. Issue 3 (May 2017) - Goto, Hiroki; Machida, Junichiro; Shibata, Akio; Tatematsu, Tadashi; Osumi, Eriko; Miyachi, Hitoshi; Takahashi, Katsu; Nakayama, Atsuo; Higashi, Yujiro; Nagao, Toru; Shimozato, Kazuo; Tokita, Yoshihito
Abstract: Cleidocranial dysplasia (CCD; MIM119600 ) is a rare autosomal-dominant inherited disorder that causes an abnormal skeletal genesis characterized by short stature, absent or delayed closure of cranial sutures, hypoplastic or absent clavicles, and dental anomalies, such as delayed tooth eruption of permanent teeth, hypodontia, and supernumerary teeth. It has been demonstrated that hypomorphic or haploinsufficiency of the runt related transcription factor 2 ( RUNX2/CBFA1 ) gene is causative for CCD. RUNX2 encodes an osteoblast-specific transcription factor, which recognizes specific DNA sequences via the runt domain, and has an important role in the differentiation of osteoblasts and the maturation of chondrocytes. In this study we describe a case of a 9-year-old Japanese male with CCD who carries a novel mutation in the RUNX2/CBFA1 gene (c.473c>a) that resulted in an amino acid substitution (p.A158E) in the runt domain of the gene product. Although A158E RUNX2 showed stable exogenous expression in transfected COS7 cells and a normal nuclear localization pattern, it did not show transcriptional activity in a reporter assay. This indicates that the A158E mutation in RUNX2 is causal for the CCD in our current case.